Design Research on Mathematics Education: Investigating The Progress of Indonesian Fifth Grade Students' Learning on Multiplication of Fractions With Natural Numbers - Shanty, Nenden Octavarulia; Hartono, Yusuf; Haan, Dede de; Ilma, Ratu (Journal on Mathematics Education, 2011)
This study aimed at investigating the progress of students' learning on multiplication fractions with natural numbers through the five activity levels based on Realistic Mathematics Education (RME) approach proposed by Streefland. Design research was chosen to achieve this research goal. In design research, the Hypothetical Learning Trajectory (HLT) plays important role as a design and research instrument. This HLT tested to thirty-seven students of grade five primary school (i.e.SDN 179 Palembang). The result of the classroom practices showed that measurement (length) activity could stimulate students’ to produce fractions as the first level in learning multiplication of fractions with natural numbers. Furthermore, strategies and tools used by the students in partitioning gradually be developed into a more formal mathematics in which number line be used as the model of measuring situation and the model for more formal reasoning. The number line then could bring the students to the last activity level, namely on the way to rules for multiplying fractions with natural numbers. Based on this findings, it is suggested that Streefland's five activity levels can be used as a guideline in learning multiplication of fractions with natural numbers in which the learning process become a more progressive learning.Keywords: multiplication fractions with natural numbers, measurement (length) activity, design research, Hypothetical Learning Trajectory, model of, model for